The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21776/ub.jam.2017.015.02.16
|View full text |Cite
|
Sign up to set email alerts
|

Technopreneurship Intentions in Faculty of Computer Science Brawijaya University Students

Abstract: This study investigates whether information technology students participation within factors such as desirability and feasibility affects Creativity and Technopreneurship Intentions before or after their graduation. Using a sample of 187 students within computer science faculty, Brawijaya University, this study finds that participation in desirability and feasibility and Creativity is positively associated with measured Technopreneurship Intentions. Sem-pls analysis methods with SPSS and Warp-PLS is implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…yang dibutuhkan dan keberlanjutannya, adalah dengan memperhatikan kebutuhan bagi negara terbelakang dan berkembang untuk menyadari dan mulai mempromosikan serta menyesuaikan technopreneurship sebagai cara dalam memenuhi kebutuhan hidup [20]. Adanya faktorfaktor keinginan dan kelayakan yang dimiliki oleh seseorang akan mempengaruhi kreativitas dan niat dalam melakukan technopreneurship [21]. Demikian juga dengan penelitian yang dilakukan Santosa mengungkapkan bahwa adanya faktor kebutuhan akan prestasi, dan efikasi diri, kesiapan instrumen, gender, prestasi akademik dan pengalaman kerja juga akan mempengaruhi intensi berwirausaha yang berbasis pada teknologi [22].…”
Section: Technopreneurshipunclassified
“…yang dibutuhkan dan keberlanjutannya, adalah dengan memperhatikan kebutuhan bagi negara terbelakang dan berkembang untuk menyadari dan mulai mempromosikan serta menyesuaikan technopreneurship sebagai cara dalam memenuhi kebutuhan hidup [20]. Adanya faktorfaktor keinginan dan kelayakan yang dimiliki oleh seseorang akan mempengaruhi kreativitas dan niat dalam melakukan technopreneurship [21]. Demikian juga dengan penelitian yang dilakukan Santosa mengungkapkan bahwa adanya faktor kebutuhan akan prestasi, dan efikasi diri, kesiapan instrumen, gender, prestasi akademik dan pengalaman kerja juga akan mempengaruhi intensi berwirausaha yang berbasis pada teknologi [22].…”
Section: Technopreneurshipunclassified
“…Findings revealed that the factors that contribute to the success of technopreneurs include access to government's initiatives, financial resources, promotion and marketing, talent pool, technology advancement, diversification of products, networks and collaboration, and business location. Mursityo et al (2017) examined the association between students' creativity in the use of technology and technopreneurship intention in Brawijaya University, Indonesia. Their findings revealed that creativity is significantly related with technopreneurship intention and concluded that students should be encouraged to adopt use of technology to complement their entrepreneurial skills for them to become technopreneurs.…”
Section: Insights From Earlier Studiesmentioning
confidence: 99%
“…From a business standpoint, there is a paradigm shift in various businesses because of the adoption of automated business process and communication channels that are designed to accomplish greater proficiency and success in business processing. This emergence of technological revolutions has unlocked new prospects and challenges to businesses (Mursityo et al, 2017;Rosly et al, 2015). The term technopreneurship is a derivative of two distinct words that is 'technology' and 'entrepreneurship'.…”
Section: Introductionmentioning
confidence: 99%
“…According to a prior study by Okorie et al (2014), technopreneurship is necessary and requires continuous attention given to the needs of developing and underdeveloped nations to become aware of, promote, and modify technopreneurship as a means of meeting basic needs. The degree to which individuals desire and are eligible determines their level of creativity and readiness for operating a technopreneurship (Mursityo, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%